2011
DOI: 10.1007/s12011-011-9151-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copper on Levels of Collagen and Alkaline Phosphatase Activity from Chondrocytes in Newborn Piglets In Vitro

Abstract: The effects of different concentrations of copper on collagen content and alkaline phosphatase (AKP) activity from chondrocytes in newborn piglets were measured. Chondrocytes were cultured in media containing 15% fetal calf serum supplemented with 0, 15.6, 31.2, and 62.5 μmol/L copper in a 12-well culture plate. Collagen content and AKP activity from the chondrocyte extracellular matrix increased significantly in the culture media with 15.6, 31.2, and 62.5 μmol/L copper and was the highest at 31.2 μmol/L coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…(Yassin et al, 2015;Chen et al, 2020). Furthermore, copper supplementation in meals has been shown to reduce the severity of osteoarthritis and other developing cartilage lesions, owing to improved collagen cross-linking and increased collagen type II production (Yuan et al, 2011). Also, the obtained results agreed with previous reviews as it shows reduction in aggrecan immunostaining intensity was less pronounced in both mild and severe osteoarthritis treated group.…”
Section: Discussionsupporting
confidence: 83%
“…(Yassin et al, 2015;Chen et al, 2020). Furthermore, copper supplementation in meals has been shown to reduce the severity of osteoarthritis and other developing cartilage lesions, owing to improved collagen cross-linking and increased collagen type II production (Yuan et al, 2011). Also, the obtained results agreed with previous reviews as it shows reduction in aggrecan immunostaining intensity was less pronounced in both mild and severe osteoarthritis treated group.…”
Section: Discussionsupporting
confidence: 83%
“…Supplementation of dietary copper has been reported to reduce the severity of osteochondrosis and other developmental cartilage lesions, which may result from enhanced collagen cross-linking and increased collagen II synthesis (Knight et al, 1990;Hurtig et al, 1993;Yuan et al, 2011). The chondroprotection efficacy of copper may be attributable to the anti-catabolic effects of Cu 2+ , which abrogates the degradation of cartilage matrix proteoglycan via inhibition of nitric oxide release (Pasqualicchio et al, 1996).…”
Section: Chondroprotective Effects Of Copper In Cartilagementioning
confidence: 99%
“…Gupta [63] believed that copper inhibited acid phosphatase activity and alkaline phosphatase activity, and in turn greatly inhibited RNA synthesis. Yuan's study [64] indicated that copper could promote AKP activity. The significant difference was observed after eight days' incubation and the highest AKP value was obtained in the culture media with 31.2 μmol L −1 (4.99 mg L −1 ) copper ions; and furthermore Cu ion reduced the AKP [64].…”
Section: Discussionmentioning
confidence: 99%